Blue Ocean Strategy Analysis PT. Kalbe Farma Tbk - Ayu Pitaloka, Adelia Intan Diah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study case to analyse the blue ocean strategy of PT. Kalbe Farma Tbk. PT Kalbe Farma Tbk. is one of the international companies engaged in manufacturing pharmaceuticals, supplements, nutrition, and health services with the motto The Scientific Pursuit of Health for a Better Life. Kalbe uses an innovative strategy done with market penetration, market development, and existing product development. Market penetration is carried out through many collaborations with companies or local distribution in each country through the subsidiary Kalbe International Pte. It is hoped that with the development of the market, Kalbe can achieve its growth targets in terms of sales as well as profit. As for product development, Kalbe developed a program called Health and Happiness, or a program for happy living, and the program produced the H2 Cordyceps Militaris product, which is a supplement that increases immunity.